2016
DOI: 10.1007/s10863-015-9640-x
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic copper coordinated complexes (Casiopeinas) uncouple oxidative phosphorylation and induce mitochondrial permeability transition in cardiac mitochondria and cardiomyocytes

Abstract: Copper-based drugs, Casiopeinas (Cas), exhibit antiproliferative and antineoplastic activities in vitro and in vivo, respectively. Unfortunately, the clinical use of these novel chemotherapeutics could be limited by the development of dose-dependent cardiotoxicity. In addition, the molecular mechanisms underlying Cas cardiotoxicity and anticancer activity are not completely understood. Here, we explore the potential impact of Cas on the cardiac mitochondria energetics as the molecular mechanisms underlying Cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…For these cell lines, twenty-four hours after they were plated, the different treatments were added and then the treated cells were incubated for 48 h. Cytotoxicity was assessed, for both cell lines, by the AlamarBlue® assay (Invitrogen, Eugene, OR) according to the manufacturer instructions. The half maximal inhibitory concentration (IC 50 ) was determined using the software Origin (Northampton, MA), as previously reported 43 . All experiments, and their respective controls, were performed in triplicates.…”
Section: Methodsmentioning
confidence: 99%
“…For these cell lines, twenty-four hours after they were plated, the different treatments were added and then the treated cells were incubated for 48 h. Cytotoxicity was assessed, for both cell lines, by the AlamarBlue® assay (Invitrogen, Eugene, OR) according to the manufacturer instructions. The half maximal inhibitory concentration (IC 50 ) was determined using the software Origin (Northampton, MA), as previously reported 43 . All experiments, and their respective controls, were performed in triplicates.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments in rat hearts have shown that Cas markedly depress contractility and reduce ATP and phosphocreatine (PCr) pools [ 10 ]; however, the precise mechanisms behind these responses are still not well understood. Recently, in vitro experiments with isolated cardiac mitochondria have shown that Cas increased the oxygen consumption rate at basal respiration and depolarized mitochondrial membrane potential, suggesting that Cas act as mitochondrial uncouplers [ 8 ]. In addition, the immunosuppressant cyclosporine A (CsA) inhibited Cas-induced mitochondrial swelling and depolarization, proposing the involvement of the permeability transition pore opening (MPT) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in vitro experiments with isolated cardiac mitochondria have shown that Cas increased the oxygen consumption rate at basal respiration and depolarized mitochondrial membrane potential, suggesting that Cas act as mitochondrial uncouplers [ 8 ]. In addition, the immunosuppressant cyclosporine A (CsA) inhibited Cas-induced mitochondrial swelling and depolarization, proposing the involvement of the permeability transition pore opening (MPT) [ 8 ]. Highlighting its importance, the MPT opening has been associated with matrix swelling and the release of small proapoptotic proteins, such as cytochrome c and oxidative damage of protein or lipids [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this shortcoming, recent anticancer screening of copper(II) complexes still shows promising in vitro results [ 13 15 ]. However, recent in vivo studies of copper compounds are few and the tested compounds are copper(II) schiff base derived from 3-(3-phenyl-allylidene)pentane-2,4-dione, copper(II) thiosemicarbazone, trinuclear CuSn 2 (Trp) complex, copper carbonate-folic conjugated nanoparticles and Casiopeína’s group of copper(II) complexes [ 16 20 ]. In vivo administration of a copper(II) thiosemicarbazone, Cu(GTSC) significantly inhibited tumor growth in HCT116 (colon cancer cell line) xenografts in nude mice [ 17 ].…”
Section: Introductionmentioning
confidence: 99%